Budesonide-hydroxypropyl-beta-cyclodextrin inclusion complex in binary poloxamer 407/403 system for ulcerative colitis treatment: A physico-chemical study from micelles to hydrogels - Santos Akkari, Alessandra Cristina; Ramos Campos, Estefania Vangelie [UNESP]; Keppler, Artur Franz; Fraceto, Leonardo Fernandes [UNESP]; Paula, Eneida de; Tofoli, Giovana Radomille; Araujo, Daniele Ribeiro de (Elsevier B.V., 2016)
Budesonide (BUD) is a glucocorticoid widely used for the treatment of ulcerative colitis. In this work, we propose the study of the system BUD-HP-beta-CD inclusion complex incorporated into PL 407 and PL407-PL403 thermoreversible hydrogels, considering physico-chemical and pharmaceutical aspects. Complexation between BUD and HP-beta-CD was confirmed by phase solubility studies (1:1 stoichiometry, Kc = 8662.8 M-1), DSC, FTIR and microscopy analyzes. BUD solubility in simulated upper and lower colon fluids was improved in a dependence of HP-beta-CD and PL 407 or PL407-PL403 association. Micellar hydrodynamic diameter studies showed the interaction between HP-beta-CD and PL blocks, as well as the reorganization of the micellar system in the presence of BUD and its inclusion complex. Micellization temperature (T-m) was not shifted, but sol-gel phase transition studies showed that in the presence of BUD, HP-beta-CD or BUD:HP-beta-CD complex, the association PL407-PL403 favored the gel formation close to the physiological temperature. Physico-chemical and in vitro release assays studies revealed no competitive displacement of BUD from the HP-beta-CD cavity evoked by PL407 or PL407-PL403 addition. These findings point out the BUD-HP-beta-CD in PL-based hydrogels as strategies for future investigations on development of new pharmaceutical formulations for the treatment of ulcerative colitis. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Budesonide; Cyclodextrin; Poloxamer; Micelle; Hydrogel; Ulcerative colitis; Polyrotaxane